2014
DOI: 10.5858/arpa.2012-0725-oa
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell-Free DNA in Sickle Cell Disease: Is It a Potentially Useful Biomarker?

Abstract: Context.—Vascular occlusion in sickle cell disease causes increased levels of plasma cell-free DNA as a result of cell death and tissue damage. Objectives.—This study investigates plasma cell-free DNA concentrations in sickle cell disease patients, and aims at exploring the significance of plasma cell-free DNA as a potential biomarker in predicting its complications. Design.—Plasma cell-free DNA levels were measured using real-time quantitative polymerase chain reaction to quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The circulating cell-free DNA in SCA patients even at steady state can be recognized by TLR9 [61,62]. Perhaps in Journal of Immunology Research our SCA patients at steady state, the hemolysis process and the release of heme are contained, not releasing sufficiently high concentrations to induce upregulation of TLRs 2 and 4, however sufficient to induce TLR9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating cell-free DNA in SCA patients even at steady state can be recognized by TLR9 [61,62]. Perhaps in Journal of Immunology Research our SCA patients at steady state, the hemolysis process and the release of heme are contained, not releasing sufficiently high concentrations to induce upregulation of TLRs 2 and 4, however sufficient to induce TLR9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with previous studies where wide variability in the mean of cfDNA concentrations was also observed [ 7 , 28 , 29 ]. It should be noted also that the kinetics of genotoxic damage-related cfDNA release into the bloodstream and its subsequent clearance have not yet elucidated [ 30 ] thus making the cfDNA, as rightly Danese et al said, a “hard to read” analyte [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphosphates may be released by activated platelets (55) and an increased number of circulating microparticles are described in SCD (see below). In addition, increased levels of cell-free DNA and nucleosomes released by activated neutrophils, and possibly other cells, have been detected in the plasma of SCD patients at “steady state,” with accentuated levels during acute painful episodes and acute chest syndrome (5658). Kininogen deficient mice transplanted with bone marrow from Townes sickle mice show lower levels of plasma TAT compared to normal kininogen littermates (59).…”
Section: Hemostatic Alterations Of Scdmentioning
confidence: 99%